Avances en nutrición acuicola con plukenetia volubilis (sache-inchi) como sustituto proteico en formulacion de alimento balanceado - Vera Olarte, Paulo Alexander (Machala : Universidad Técnica de Machala, 2020)
The Aquaculture and Pisciculture activity in Ecuador is well developed by the variety of organisms that are mainly grown shrimp and tilapia, due to the great demand that exists in the local and international market generating employment and foreign exchange for the country, and financial income to thousands of persons. Taking into account that these crops need balanced food and that the cost of production of these products reaches up to 60% of their item, it is necessary to lower their value without deteriorating the quality of it. Studies related to the field of aquaculture nutrition with the application of the Sacha inchi cake by-product have been able to determine the positive effect on both omnivorous and carnivorous organisms in captivity, partially or totally minimizing the consumption of fishmeal proteins, inputs used Due to its excellent nutritional qualities, but due to its high cost and shortage they have made the production of balanced foods more expensive. All of the above has allowed us to accept the use or application offered by Sacha inchi flour for having a high contribution of proteins, vitamins, carbohydrates, lipids, minerals and omega oils 3-6-9 that aquatic and terrestrial organisms need to be able to develop and grow faster by shortening and thus reducing production cycles without affecting the quality of the product and its supply in the environment Therefore, the objective of this work is to highlight the benefits offered by Sacha inchi cake (Plukenetia volubilis) as a protein substitute in aquaculture nutrition.
La actividad Acuícola y Piscícola en Ecuador está bien desarrollada por la variedad de organismos que se cultivan principalmente. Debido a la gran demanda que existe en el mercado local e internacional generando empleo y divisas para el país, e ingresos financieros a miles de personas. Teniendo en cuenta que estos cultivos necesitan del alimento balanceado y que el costo de producción de estos productos alcanza hasta el 60 % de su rubro, se hace necesario abaratar su valor sin desmejorar la calidad del mismo. Estudios relacionados en el campo de la nutrición acuícola con la aplicación del subproducto torta de Sacha inchi han podido determinar el efecto positivo en organismos tanto omnívoros como carnívoro en cautiverio, minimizando de forma parcial o totalmente el consumo de proteínas de harinas de pescado, insumos utilizados por su excelentes cualidades nutricionales pero que debido a su alto costo y escasez han encarecido la elaboración de los alimentos balanceados. Todo lo señalado ha permitido aceptar el uso o la aplicación que ofrece la harina de Sacha inchi por poseer un elevado aporte de proteínas, vitaminas, carbohidratos, lípidos, minerales y aceites omegas 3-6-9 que los organismos acuáticos y terrestres necesitan para poder desarrollarse y crecer más rápido acortando y abaratando así los ciclos de producción sin afectar la calidad del producto y su abastecimiento en el medio. Por lo tanto, el objetivo de este trabajo es resaltar los beneficios que ofrece la torta de Sacha inchi (Plukenetia volubilis) como sustituto proteico en la nutrición acuícola.
Keywords: HARINA; SACHA; NUTRICIÓN; PECES